Development of an Internet–Based System to Measure Thermal Comfort in Indoor Environments - Sanbasivam, Sivasankar (2006)
The aim of the research is develop an internet-based system that would act as an advisor to determine and predict comfort level in indoor environment based on fundamental indoor parameters, with the goal that development of a system that determines the desirable comfort level in buildings that will enable the saving of energy and ultimately result in saving of costs for cooling of buildings and yet at the same time provide optimum comfort for the occupants. Air-conditioning temperatures are often set between 23°C to 25°C based on American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) requirements, but it is not suitable for Malaysians. With this system, room temperatures can potentially be increased by at least 0.5°C. In the long term, the system has a potential to reduce energy consumption without sacrificing Thermal Comfort for occupants.The technology system used in the development of Thermal Comfort System for Malaysia (TCSM) is based on Active Server Pages (ASP) server technology written in Visual Basic Script (VBScript) using Macromedia Dreamweaver MX as the web-authoring program of choice. Fanger’s equations for predicting Thermal Comfort were converted into specific sets of rules using the backward chaining method. The system is designed to follow three main sections mainly the Start TC Helper, TC Predictor and Thermal Comfort Information. The major input variables required by the system from the user are (1) air temperature of the room, (2) mean radiant temperature of the room, (3) air velocity of the room, (4) relative humidity of the room, (5) clothing thermal resistance of the user and (6) the metabolic rate of the user. As a means of validation of the system, studies were carried out in the Mid-Valley shopping centre, KBP001 Engineering lab and BKB 107A room from the Faculty of Engineering. As a means of verification, interviews were also carried with various experts in the field of thermal comfort in Malaysia and as a result of the interviews Humphreys’ adaptive thermal comfort equation was added to the internet-based system. With the use of the system, there is a potential savings in energy bills when the system is used to offer the user the comfortable temperature of the room.